The Impact of Using Social Media in the Learning Process on Student Social Interaction - Guilin, Xie; Xu, Shanshan; Xavier, Murphy; Elliot, McCarty (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background:Social media is a digital platform that allows users to carry out social activities and communicate. Likewise in education, the impact of using social media in the learning process has various impacts. Although social media can increase student motivation and broaden horizons, social media can also make student behavior deviant. Research purposes:This research was conducted with the aim of knowing the impact of using social media in the learning process, namely to understand how the use of social media affects students' social interactions. Does this influence have a positive or negative impact? Method:In conducting this research, researchers used quantitative methods in carrying out the research. The data obtained by the researcher was obtained through distributing questionnaires presented by the researcher via a goggle from application. The distribution of this questionnaire is carried out by researchers online, and then the results of the distribution of this questionnaire will be processed using an SPSS application. Results:From this research conducted, researchers can conclude the research results that the use of social media can help students in the learning process and increase knowledge. However, its use can also cause students' social behavior to become deviant, such as excessive use of social media, laziness in studying, irregular allocation of time for studying, and so on. Conclusion:Based on the results of this research which discusses the impact of using social media in the learning process on social media interactions, social media has advantages and disadvantages in its use. However, students must be able to use social media wisely, so that deviant behavior does not occur in using social media